Experiencias etnoeducativas en Bogotá (2021)
The following work presents the research carried out on the different ethno-educational experiences documented in official schools of the city of Bogotá in order to make visible and identify the challenges, scope and achievements in which the ethnoeducation projects of Afro-descendant ethnic communities are currently found. , indigenous and rom of the city. Two characteristics were identified: 1. The reduced content of ethno-educational experiences available for online consultation on ethno-education of the aforementioned ethnic communities, especially the Roma; and 2. The importance of linking, in the construction of ethno-educational scenarios, to other disciplines of traditional knowledge in order to create curricular plans based on cultural diversity for the realities of ethnic groups in Bogotá.